Role of HRCT in temporal bone trauma vis-à-vis site of facial nerve injury: a pilot study - Munjal, Manish; Mehndiratta, Anju; Khurana, Harneet; Munjal, Shubham; Khurana, Ajit Singh; Kalra, Shivam; Bansal, Ishan; Sharma, Robin (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Facial nerve paralysis in head injuries has a lesion in the bony fallopian canal. The line of fracture and site of lesion was studied using high resolution computed tomography. Methods: A prospective study of 37 subjects of facial nerve paralysis following head injury was undertaken. The patients were selected from the neurosurgical trauma centre of a tertiary care facility, of Dayanand Medical College, Ludhiana, during a period of one and a half years. HRCT was performed taking 2 mm axial and coronal cuts of temporal bone for all patients to analyse the type and site of fracture of the bony facial canal. Results: Total 19 (51.3%) patients had longitudinal fractures while transverse fracture was seen in 7 (18.9%) patients and 11 (29.7%) patients showed comminuted fracture on HRCT. Perigeniculate region was involved in 4 (44.4%) patients. Tympanic segment was affected in 3 (33.3%) patients and the mastoid segment in 4 (44.4%). The tympanic and the mastoid segments were involved simultaneously in two patients. These findings correlated with those observed on HRCT. 500 patients of head injury were screened and 48 (9.6%) patients were found to have facial nerve paralysis. 44 (91.67%) of these were males and 4 (8.33%) females. Majority of the patients (62.5%) were between the age group of 21-40 years. Conclusions: In the present study of facial paralysis post head injury, longitudinal facial fractures were commonest followed by mixed and transverse on HRCT. The pregeniculate and the mastoid segments showed an equal incidence followed by the tympanic segment.